A study to assess cardiac diseases in pregnancy and pregnancy outcome - Gore, Sushma; Warade, Shrikant; Bramhapurikar, Roocha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Heart disease has a significant impact on fetal and maternal health during pregnancy, labor and delivery. In India and other developing countries, rheumatic heart disease is most common. Cardiac disorders are observed in approximately 1% of pregnancies; they account for morbidity and mortality rates. The objective of the study was to analyze the effect of cardiac diseases on maternal and fetal outcome. Methods: Hospital based cohort study was done for a period of 5 years. All pregnant women with cardiac disease were the study participants. Total numbers of women with cardiac disease were 390. Results: It was observed that majority of the study participants were suffering with mitral stenois (30%), followed by mitral regurgitation (25%) and mitral strenosis and regurgitation (12%). Very few women died because of certain complications, atrial fibrillation (1%), congestive cardiac failure (1%) and pulmonary embolism (1%). The overall perinatal mortality was found to be 4% in the present study. Conclusions: Proper screening of the pregnant women to rule out any cardiac disease is required. If timely intervention are taken to treat the pregnant women with cardiac disease the morbidity and mortality in mother and foetus can be prevented to a great extent.